Perbedaan Tanggung Jawab Direksi Sebagai Personal Guarantee Dan Penyebab Kerugian Perseroan Terbatas - Fatika Sari (Officium Notarium, 2022)
The Board of Directors as an organ of a Limited Liability Company that establishes legal relations can be held partly responsible for taking actions beyond their authority, but there is another situation where the directors can be held responsible for the failure of a legal relationship due to being a personal guarantee, thus an in-depth study is needed regarding the differences between the two circumstances. the. The problem formulated is how the different responsibilities of the Board of Directors as a personal guarantee and as a cause of loss to the Limited Liability Company. The research method used is normative, with a statutory approach and a conceptual approach. The data collection technique used was library research that is analyzed descriptively. The results of the study conclude that the responsibility of the directors as a personal guarantee is born when the company is no longer able to pay or carry out its engagements; The responsibility of the directors as the cause of the loss of the Limited Liability Company arises when it is proven that the directors are negligent and guilty.Key Word: Responsibility, Director, Personal Guarantee, Limited Liability Company AbstrakDireksi sebagai organ Perseroan Terbatas yang membangun hubungan hukum dapat ikut bertanggung jawab karena melakukan tindakan diluar kewenangannya, namun terdapat suatu keadaan lain di mana direksi dapat dituntut untuk ikut serta bertanggung jawab atas kegagalan hubungan hukum karena menjadi personal guarantee maka diperlukan pengkajian mendalam mengenai perbedaan kedua keadaan tersebut. Masalah yang dirumuskan ialah bagaimana perbedaan tanggung jawab Direksi sebagai personal guarantee dan sebagai penyebab kerugian Perseroan Terbatas. Metode penelitian yang digunakan adalah normatif, dengan pendekatan perundang-undangan dan pendekatan konseptual. Kemudian teknik pengumpulan data yang digunakan adalah studi Pustaka dan selanjutnya dianalisis secara deskriptif. Hasil penelitian menyimpulkan pertanggungjawaban direksi sebagai personal guarantee lahir ketika perseroan tidak lagi mampu untuk membayar atau melaksanakan perikatan; pertanggungjawaban direksi sebagai penyebab kerugian Perseroan Terbatas lahir ketika terbukti direksi tersebut lalai dan bersalah.Kata-kata Kunci: Tanggung Jawab, Direksi, Personal Guarantee, Perseroan Terbatas